2020
DOI: 10.1177/0333102420956705
|View full text |Cite
|
Sign up to set email alerts
|

Cluster headache not responsive to sumatriptan: A retrospective study

Abstract: Introduction Subcutaneous sumatriptan, a 5HT1B/1D agonist, is the most effective drug in cluster headache acute treatment. About 25% of the patients do not respond to subcutaneous sumatriptan; the reasons for this are unknown. In this study, we compare clinical characteristics of cluster headache patients responding and non-responding to subcutaneous sumatriptan. Methods We retrospectively investigated the clinical records of 277 cluster headache patients. Patients reporting repeated satisfactory response to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Hence, though there is no interictal burden without an ictal burden, focusing solely on the latter implies missing an opportunity to relieve distress because drugs cannot prevent or abort all attacks. 8,9 Based on these findings, we advocate broadening the therapeutic goals and attempting to maximise the QoL. This approach embraces the idea of patient-centred care, which holds that considering patients' families in the personalised care plan may facilitate meeting the objective of emotional-not just physical-well-being.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, though there is no interictal burden without an ictal burden, focusing solely on the latter implies missing an opportunity to relieve distress because drugs cannot prevent or abort all attacks. 8,9 Based on these findings, we advocate broadening the therapeutic goals and attempting to maximise the QoL. This approach embraces the idea of patient-centred care, which holds that considering patients' families in the personalised care plan may facilitate meeting the objective of emotional-not just physical-well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, though there is no interictal burden without an ictal burden, focusing solely on the latter implies missing an opportunity to relieve distress because drugs cannot prevent or abort all attacks. 8,9…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other real-world studies have noted that patients can obtain relief from less than 6 mg (15) and there appears to be no tachyphylaxis (14,16,17). Studies of predictors for triptan response have shown that patients with eCH (as opposed to cCH), younger patients, and patients with shorter and less frequent attacks may be more responsive to triptans (1820). One genetic study identified a common GNB3 variant as a predictor of triptan response in CH (21), though testing for GNB3 is not commonplace in clinical practice.…”
Section: Acute Pharmacological Treatmentsmentioning
confidence: 99%